(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
Permanent magnet–assisted synchronous reluctance motors (PMa-SynRMs) are promising for electric vehicles due to high torque density and lower magnet use, yet torque ripple remains a challenge. This paper presents the design and optimization of a six-phase PMa-SynRM to minimize torque ripple while preserving average torque and back-EMF quality. Key rotor parameters, slot pitch, barrier-end geometry, insulation ratio, and magnet width, are optimized via the Taguchi method. Performance is evaluated using finite element analysis (FEM). The optimized design significantly reduces torque ripple, maintains average torque, and improves the back-EMF harmonic profile. Thermal analysis confirms safe operation of magnets and windings under rated conditions. The results demonstrate that the proposed approach effectively enhances electromagnetic performance while ensuring thermal reliability.